Perioperative Use of Anticoagulant and Platelet-inhibiting Medications for Elective Spine Surgery: Results of a Nationwide Survey - Baschera, Dominik; Oberle, Joachim; Grubhofer, Florian; Schmid, Samuel Luca (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims Perioperative use of anticoagulant and platelet-inhibiting agents by patients undergoing spine surgery poses the dilemma of increased risk of hemorrhage. We examined the standards of use for these medications and expert opinions through a nationwide survey.Materials and Methods An online-based survey was conducted by invitation. A personal token to access the survey was sent to one representative of each neurosurgical and orthopaedic unit performing spine surgery and to all other active members of the Swiss Society of Neurosurgery and the Swiss Society of Spinal Surgery. A total of 97 e-mail invitations were sent to 19 representatives of neurosurgical or orthopaedic units and 78 registered neurosurgeons and orthopaedic surgeons who potentially perform spine surgery.Results From February to April 2016, 40 surgeons (26 neurosurgeons, 14 orthopaedic surgeons) completed the survey (41%). Among the respondents, 55% prescribed prophylactic heparin preoperatively; depending on the procedure, 83 to 95% prescribed heparin postoperatively. Depending on the type of surgery, 23 to 48% discontinued acetylic acid preoperatively, and 80 to 87% always discontinued clopidogrel preoperatively. On average, platelet inhibition was resumed 4 ± 2.5 days postoperatively. Orthopaedic surgeons recommenced platelet inhibition earlier than neurosurgeons (p = 0.013). Anticoagulation with rivaroxaban was discontinued 3 ± 2 days before surgery. Depending on the indication, 72 to 98% of respondents temporarily replaced traditional anticoagulation therapy (vitamin K antagonists) with heparin perioperatively.Conclusion Administration and discontinuation of anticoagulant and platelet-inhibiting medications in the perioperative setting of spinal surgery differ vastly between different units and surgeons. Recommendations from the spine surgeon societies may be helpful to develop nationwide guidelines.
Keywords: anticoagulation; platelet inhibition; spine; surgery